Trend in distribution pattern of anaemia in children 6 months to 5 year: a prospective hospital based study - Shankar, Poornima; Patel, Shruthi (International Journal of Contemporary Pediatrics, 2018)
Background: Anaemia is a global Public health problem, in our study we aimed at assessing trend in the distribution pattern of anaemia and etiology among the children. Methods: It’s a prospective study conducted in Department of Pediatrics, KIMS Bangalore for a period of 1 years. Children aged 6 months to 5 years admitted in ward for various purposes in whom Hb value is suggestive of anaemia according to WHO guidelines were included after consent and were further evaluated for the cause of anaemia. Results: Total 435 cases met our inclusion criteria, out of which 147 cases gave consent for further workup and were enrolled in the study. 81 cases of mild anaemia, 42 cases of moderate anaemia, and 24 cases of severe anaemia were reported. Further, most common etiology in all groups was Iron deficiency anaemia. Nutritional Anaemia was most commonly seen in low socio-economic background. Conclusions: Nutritional anaemia is the most common etiology found in our study. By improving nutritional status we can improve the quality of life in children.